Collaboration of primary care and public health at the local level: observational descriptive study of French local health contracts - Kendir, Candan (Prim Health Care Res Dev, 2020)
AIM: In this paper, we report on a study investigating the involvement of primary care providers in French local health contracts. BACKGROUND: Worldwide actions are carried out to improve collaboration between primary care and public health to strengthen primary healthcare and consequently community health. In France, the local health contract is an instrument mobilising local stakeholders from different sectors to join in their actions to improve the health of the population. METHODS: We developed an instrument to analyse the frequency and nature of involvement of primary care providers in 428 action plans extracted from a sample of 17 contracts (one per French region). The number of primary care actions were counted, and thematic analyses were conducted to identify the nature and level of involvement of the professionals. FINDINGS: Primary care providers were involved in 20.1% (n = 86) of the action plans and were mostly described as a target of the action rather than leaders or partners. Within those action plans, 76.7% (n = 66) of these action plans aimed to improve access to care for local communities; an issue that appears as the main driver of collaboration between public health and primary care actors.